DRUG-RESISTANCE AND COMPENSATORY MUTATIONS IN MYCOBACTERIUM TUBERCULOSIS - Auganova, D.; Akisheva , A.; Tsepke , A.; Tarlykov , P. (Eurasian Journal of Applied Biotechnology, 2023)
Gram-positive bacteria of Mycobacterium tuberculosis complex (MTBC) are causative agents of tuberculosis disease. According to the report of the World Health Organization, tuberculosis is one of the leading causes of mortality worldwide. Moreover, epidemiological data shows that due to the COVID-19 pandemic tuberculosis mortality has risen in comparison with previous years. Drug resistance is another threatening issue when the resistance to antitubercular (anti-TB) drugs makes therapy less effective. Furthermore, drug resistance is often burdened with compensatory mechanisms that overcome fitness defects related to drug-resistant mutations. This review discusses the drug resistance and compensatory mutations in Mycobacterium tuberculosis and the current situation with anti-TB drug resistance in the Republic of Kazakhstan.